Susceptibility of ancient wheat species to storage pests Sitophilus granarius and Tribolium confusum. (September 2019) - Gałęcki, Remigiusz; Bakuła, Tadeusz; Wojtacki, Michał; Żuk-Gołaszewska, Krystyna
Abstract: The feeding behavior of storage pests colonizing the spikelets of ancient wheats remains insufficiently investigated. Therefore, the aim of this study was to determine the susceptibility of emmer, spelt and common wheat grown under different agronomic conditions to storage pests, including the granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae) and the Tribolium confusum (du Val) (Coleoptera: Tenebrionidae). The experiment was performed on the spikelets of two non-free-threshing wheat species, spelt Triticum spelta (L.) cv. Wirtas and emmer Triticum diccocon (Schrank) cv. Bondka, and the grain of free-threshing common wheat Triticum aestivum (L.) cv. Bombona. The remaining experimental factors were different nitrogen fertilization rates and the application of a growth regulator. Two storage pest species, the S. granarius and the T. confusum, were introduced to the experimental grain and spikelets. The results after 6 months revealed that different nitrogen fertilization rates, the application of the growth regulator and wheat species did not affect the population size of S. granarius . After 12 months of incubation, no significant changes were found in the abundance of T. confusum in response to nitrogen fertilization, growth regulator or wheat species. After 12 months of incubation, wheat species exerted an inhibitory effect on the population size of S. granarius . Spelt was the most resistant and common wheat was the least resistant wheat species. The results of this study indicate that spelt was most resistant to storage pests, whereas common wheat grain was most abundantly colonized by storage pests. Highlights: The population size of wheat weevils was influenced by wheat species. Spelt was the most resistant and common wheat was the least resistant species. Fertilization and growth regulator had no significant effects on storage pests. Spelt spikelets were most resistant to wheat weevils and confused flour beetles. No linear correlations were observed between protein content and pest population.